Tinjauan Yuridis Hak Karyawan PT Kuoni Indonesia dalam Hal Terjadinya Pemutusan Hubungan Kerja Berdasarkan Undang – Undang Nomor 13 Tahun 2003 - Cecep Bihar Aftarudin; Arihta Esther Tarigan; Elianta Ginting (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
An employment relationship is a relationship between a worker and an employer or entrepreneur involving work, wages, and orders. One outcome of this employment relationship is termination of employment. To create a just and prosperous society based on Pancasila and the 1945 Constitution, the government has enacted laws concerning termination of employment, such as Law No. 13 of 2003 concerning Manpower, Law No. 11 of 2020 concerning Job Creation, and Government Regulation No. 35 of 2021 concerning Fixed-Term Employment Agreements, Outsourcing, Working and Rest Hours, and Termination of Employment. This research uses a normative legal method, namely examining the law as it exists or should exist, or the law in books. The research was conducted by analyzing applicable laws and regulations, using library materials or secondary data covering primary, secondary, and tertiary law. Termination of employment is the right of both parties, namely workers and employers. Both parties can terminate the employment relationship according to their respective situations or conditions. This issue often generates debate because each party has different perspectives and arguments regarding termination of employment. As a result, the amount of compensation workers receive in practice also varies. Comparing Law No. 13 of 2003, Law No. 11 of 2020, and Government Regulation No. 35 of 2021 concerning termination of employment, it is clear that the Employee Rights Act No. 13 of 2003 provides more compensation than the Job Creation Law. Therefore, in practice, many companies, including PT Kuoni Indonesia, seek ways to reduce their compensation obligations under the pretext of negotiating with employees.